Knowledge and practice of obstetric care providers on prevention of obstetric fistula 2023: an institution-based cross-sectional study - Alemu, Solomon Seyife; Agago, Mahlet Tesfaye; Ukumo, Eshetu Yisihak; Hadero, Tesfahun Simon (Frontiers in Global Women's Health, 2023)
Background Obstetric fistula is a preventable devastating condition that is mostly caused by obstructed labour. About 22% of obstructed labor is complicated by obstetric fistula. Skilled birth attendants during delivery are essential for the prevention of obstetric fistula. However, little is known about the status of the knowledge and practice of obstetric fistula prevention in the Gamo zone. Objective We aimed to assess the knowledge, practice, and associated factors of obstetric caregivers on the prevention of obstetric fistula in public health facilities of the Gamo zone in southwest Ethiopia 2023. Method A cross-sectional study was employed among 372 obstetric caregivers in selected public health facilities of the Gamo zone in southwest Ethiopia from 1 December 2022 to 30 January 2023. Study participants were selected by a simple random sampling technique, and data were collected by using a pre-tested and self-administered questionnaire. The collected data were coded and entered into Epi-Data version 4.6 computer software and exported to SPSS version 27 for analysis purposes. Bivariable and Multivariable Logistic analyses were applied. The level of significance was declared at a P-value ≤0.05 and a 95% confidence interval. Results About 57% [95% CI (53.00–62.00)] of participants had good knowledge, and about 55.4% [95% CI (50.00–60.00)] of obstetric caregivers showed good practice for obstetric fistula prevention. The factors significantly associated with knowledge were service year [AOR = 2.50, 95% CI = (1.12–6.73)], types of a health facility [AOR = 1.99, 95% CI = (1.01–3.92)], age [AOR = 2.38, 95% CI = (1.03–5.49)], and in-service training [AOR = 4.61, 95% CI = (2.35–9.05)]. In-service training [AOR = 14.86, 95% CI = (12.75–18.73)], service year [AOR = 3.58, 95% CI = (1.24–10.29)], and knowledge [AOR: 13.24, 95% CI = (6.18–14.34)] were factors which were significantly associated with the practice of obstetric caregivers towards obstetric fistula prevention. Conclusion The knowledge and practice of obstetric caregivers on the prevention of obstetric fistula was low in public health facilities of the Gamo zone. In this study, practicing at a hospital was a factor significantly associated with the knowledge of obstetric caregivers. Having in-service training, advanced service year, and age were factors significantly associated with the knowledge and practice of obstetric caregivers. Regular in-service training of health professionals can enhance their knowledge and practice of obstetric fistula prevention.